2021
DOI: 10.21203/rs.3.rs-577578/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymorphism and Distribution of Ace Gene Involved in the Resistance of Musca Domestica to Organophosphates in Guizhou Province of China

Abstract: Acetylcholinesterase is the primary target of organophosphates (OPs) and carbamates in insects. As gene mutation has been verified as an important mechanism of insecticide resistance in insects, in this study, we investigated the status of OPs resistance and the polymorphism of ace gene (that encodes acetylcholinesterase) in housefly (Musca domestica L) field populations in Guizhou Province, China. Bioassays showed that the houseflies had 142.16–303.54-fold resistance to dichlorvos (DDVP) and 122.13–363.98-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In addition, the homozygous genotypes of these wild type amino acids were detected in field populations, except for the Riyadh population, where Val/Val and Gly/Gly, at positions 260 and 342, respectively, were not detected ( Table 3 ). As in other worldwide house fly populations, Val/Val homozygotes at the 342 position were not recovered [ 4 , 6 , 16 , 44 ]. Based on previous studies and this study, the three mutations at positions 260, 342, and 407 confer different levels of insecticide insensitivity in house flies [ 4 , 15 , 17 , 18 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…In addition, the homozygous genotypes of these wild type amino acids were detected in field populations, except for the Riyadh population, where Val/Val and Gly/Gly, at positions 260 and 342, respectively, were not detected ( Table 3 ). As in other worldwide house fly populations, Val/Val homozygotes at the 342 position were not recovered [ 4 , 6 , 16 , 44 ]. Based on previous studies and this study, the three mutations at positions 260, 342, and 407 confer different levels of insecticide insensitivity in house flies [ 4 , 15 , 17 , 18 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 68%
“…Walsh et al [ 15 ] reported that house fly strain 77M, possessing Leu + Ala + Tyr combination, showed 48-fold DDVP resistance compared with the wild type. This combination was also frequently detected in house fly field populations in the USA, Turkey, Japan, Kazakhstan, and China [ 4 , 6 , 16 , 17 , 35 , 48 ]. Among the 13 heterogeneous combinations, Val/Leu + Ala/Val + Tyr and Leu + Ala + Phe/Tyr were well represented in the surveyed regions.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations